2021
DOI: 10.1007/s12630-021-01958-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative hypovolemic phlebotomy on transfusion and clinical outcomes in patients undergoing hepatectomy: a retrospective cohort study

Abstract: Background There is no consensus on how to best achieve a low central venous pressure during hepatectomy for the purpose of reducing blood loss and red blood cell (RBC) transfusions. We analyzed the associations between intraoperative hypovolemic phlebotomy (IOHP), transfusions, and postoperative outcomes in cancer patients undergoing hepatectomy. Methods Using surgical and transfusion databases of patients who underwent hepatectomy for cancer at one institution (11 January 2011 to 22 June 2017), we retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Published data from our group and others have not documented any significant differences in overall postoperative complications, end-organ ischemic complications (renal, cardiac, cerebral, hepatic, and mesenteric), or perioperative mortality between HP and usual care [34,39,[41][42][43][44][45]48]. Similarly, PRICE-1 [40] and two other small trials [46,47] noted no significant differences in any adverse event metric.…”
Section: Adverse Eventsmentioning
confidence: 51%
See 2 more Smart Citations
“…Published data from our group and others have not documented any significant differences in overall postoperative complications, end-organ ischemic complications (renal, cardiac, cerebral, hepatic, and mesenteric), or perioperative mortality between HP and usual care [34,39,[41][42][43][44][45]48]. Similarly, PRICE-1 [40] and two other small trials [46,47] noted no significant differences in any adverse event metric.…”
Section: Adverse Eventsmentioning
confidence: 51%
“…Small studies in liver transplantation, living donor hepatectomy, and more recently with our own data, have suggested that HP has the potential to significantly reduce blood transfusion in elective liver surgery [39,41,43,44]. Finally, the safety profile of this intervention appears excellent [40,42,45].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…15,16 Among them, the use of an intraoperative phlebotomy has been promising. [16][17][18][19][20] An intraoperative phlebotomy consists of removing some blood in a blood donation bag at the beginning of surgery and transfusing it at the end of surgery to reduce portal hypertension and splanchnic congestion observed in end-stage liver disease (ELD) during liver dissection, thus potentially reducing blood loss and subsequent RBC transfusions. 17,18,21 In fact, this intervention has been associated with less bleeding, fewer RBC transfusions, and lower mortality in different multivariable analyses conducted in liver transplant recipients.…”
Section: Re ´Sumementioning
confidence: 99%
“…10,16,[22][23][24] Similar associations have also been recently observed in patients undergoing a liver resection. 19,20 In a recent systematic review, the use of intraoperative phlebotomy was also the only fluid management strategy associated with a lower mortality in observational studies conducted in liver transplantation. 25 The potential effects of phlebotomy in liver transplant recipients have always been assessed using conditional multivariable models not targeted specifically on the association between phlebotomies and outcomes, but rather using analyses in which phlebotomy was a variable within models that included many potential outcome determinants.…”
Section: Re ´Sumementioning
confidence: 99%